Education in the constitutions of the American Southern Cone countries - Bedmar, Vicente Llorent (2015)
The constitution of every State defines the basic regime of the rights and freedoms of citizens, and simultaneously rules their organization and development, articulating their own system of acquaintanceship and conforming in the regulatory guide of social, familiar and educational norms. Constitutions govern two very important areas for the transformation/consolidation of society: family and education. The constitutions of the studied countries - Argentina, Chile, Paraguay and Uruguay - not only recognize the high value of the family for the State and society, but also favor and protect it. They establish the basic rights of families while impose obligations on the State to benefit them. From a teleological point of view, we observe how all of them, through education, claim the development of human personality, with special support to moral aspects.